2022
DOI: 10.3390/ijms23105544
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulating the High Level of 17-Beta-Hydroxysteroid Dehydrogenase 13 Plays a Therapeutic Role for Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide, and there is no specific drug to treat it. Recent results showed that 17-beta-hydroxysteroid dehydrogenase type 13 (HSD17B13) is associated with liver diseases, but these conclusions are controversial. Here, we showed that HSD17B13 was more highly expressed in the livers of NAFLD patients, and high expression was induced in the livers of murine NAFLD models and cultural hepatocytes treated using various etiologies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
(87 reference statements)
2
11
0
Order By: Relevance
“…66 In a co-culture system, high HSD17B13 expression in hepatocytes indirectly induces HSC activation and downregulation of HSD17B13 in HFD-fed mice is associated with decreased HSC activation. 52 Although speculative, these findings suggest that the protective effect of HSD17B13 lossof-function variants on NAFLD-related liver damage might be partly via reduced HSC activity as a result of HSD17B13's depleted retinol dehydrogenase enzymatic function, which leads to increase in hepatic retinol availability across the liver (Figure 1). This hypothesis needs to be validated and the potential mechanisms of HSD17B13 investigated.…”
Section: Overexpression Of Hsd17b13 In Cultured Hepatocyte Cell Lines...mentioning
confidence: 99%
See 3 more Smart Citations
“…66 In a co-culture system, high HSD17B13 expression in hepatocytes indirectly induces HSC activation and downregulation of HSD17B13 in HFD-fed mice is associated with decreased HSC activation. 52 Although speculative, these findings suggest that the protective effect of HSD17B13 lossof-function variants on NAFLD-related liver damage might be partly via reduced HSC activity as a result of HSD17B13's depleted retinol dehydrogenase enzymatic function, which leads to increase in hepatic retinol availability across the liver (Figure 1). This hypothesis needs to be validated and the potential mechanisms of HSD17B13 investigated.…”
Section: Overexpression Of Hsd17b13 In Cultured Hepatocyte Cell Lines...mentioning
confidence: 99%
“…HSD17B13 is newly identified liver‐specific protein that localises to the surface of LDs (Figure 1). Overexpression of HSD17B13 in cultured hepatocyte cell lines leads to the increase in number and size of LDs, 36 potentially by stabilising intracellular TG content 52 . By contrast, enzymatically inactive HSD17B13 variants confer a protective effect against NAFLD progression to NASH.…”
Section: The Role Of Hsd17b13 In the Progression Of Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA concentration was determined by NanoDrop 2000 (Thermo Scientific, United States). As previously described (Wang et al, 2022), qRT-PCR was performed with the indicated primers (Table 1) and HiScriptII One Step QRT-PCR SYBR Green Kit (Vazyme, Nanjing, China) using the ABI 7500 Fast system (Applied Biosystems, United States). RNA (30-120 ng) was used as a template, and qRT-PCR amplification consisted of 5 min of reverse transcription step at 50 °C, then 5 min of an initial denaturation step at 95 °C, followed by 40 cycles of PCR at 95 °C for 10 s and 60 °C for 34 s. Target gene expression levels were Frontiers in Pharmacology frontiersin.org normalized to the internal control gene GAPDH using the 2 −ΔΔCT method.…”
Section: Quantitative Real-time Reverse Transcription Polymerase Chai...mentioning
confidence: 99%